ANALISIS KEPEMIMPINAN KEPALA DESA PEREMPUAN DALAM PROSES PENGAMBILAN KEPUTUSAN (STUDI PADA DESA GUWOKAJEN KECAMATAN SAWIT KABUPATEN BOYOLALI) - Pambayun, Aisyah Fieta; Astuti, puji -; Marlina, Neny - (Journal of Politic and Government Studies, 2025)
The involvement of women in leadership positions within the Indonesian government remains largely overshadowed by male counterparts. This situation is primarily due to gender inequality and injustice that women face in society. A similar lack of female leadership is evident in village governance in Boyolali Regency, particularly in the role of village head. This research focuses on the leadership of Evy Nurdina, the only female village head in Sawit Sub-district, overseeing Guwokajen Village. The aim of this study is to analyze how Village Head Evy Nurdina engages in the decision-making process. The research adopts a descriptive qualitative approach. Data collection methods include interviews and documentation, which are analyzed through data reduction techniques, data presentation, and drawing conclusions.The results indicate that Village Head Evy Nurdina successfully represents herself as a female leader, particularly in decision-making. She highlights traits commonly associated with female leaders, such as strong persuasive and communication skills, the ability to counter unfounded criticism effectively, a spirit of cooperation, democratic leadership capabilities, and the willingness to take risks.Consequently, her leadership showcases that women are deserving of leadership roles and possess unique characteristics in their approach, particularly in decision-making, where they often excel in verbal skills, assertiveness, and democratic principles. Recommendations from this study include providing greater opportunities for women to assume leadership roles in the public sector, especially within village governance